2019
DOI: 10.1186/s12902-019-0450-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for cervical lymph node metastasis of papillary thyroid microcarcinoma: a study of 268 patients

Abstract: Background: To investigate the risk factors of cervical lymph node (LN) metastasis in papillary thyroid microcarcinoma (PTMC) patients. Methods: We retrospectively analyzed the clinicopathologic data of all patients who received standard lobectomy for PTMC at our institution between October 2017 and January 2019. Central LNs were dissected in all patients. Lateral LNs were dissected if metastasis to the lateral LNs was suggested based on pre-op fine-needle aspiration biopsy. The relationship between variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
5
10
2
Order By: Relevance
“…According to other studies present in the literature ( 12 , 13 , 18 23 ), we found younger age, tumor size, tall cell variant of PTC, extrathyroidal extension, and angioinvasion as independent risk factors for lymph node metastases.…”
Section: Discussionsupporting
confidence: 75%
“…According to other studies present in the literature ( 12 , 13 , 18 23 ), we found younger age, tumor size, tall cell variant of PTC, extrathyroidal extension, and angioinvasion as independent risk factors for lymph node metastases.…”
Section: Discussionsupporting
confidence: 75%
“…BRAF V600E mutation has been extensively studied to date and, although its role is valuable for prognosis when associated with other clinical features, its role as single prognostic marker remains uncertain [4,[12][13][14][15][16][17][18][19]. In our population, the most common mutation was the BRAF V600E and its prevalence was higher in non-incidental mPTCs than in those incidentally found, as already reported by other authors [20,21].…”
Section: Discussionsupporting
confidence: 67%
“…PTC is one of the most common cancers in the world. Cervical lymph node metastasis might occur in the early stage with metastatic rates ranging from 20% to 50% in the existing literature 9,10 . The metastasis can be detected not only at the time of diagnosis of primary PTC, but also prior to or after the primary diagnosis.…”
Section: Discussionmentioning
confidence: 99%